Effectiveness of the My ADA Application on ANC Visiting Behavior of Pregnant Women in the Cities of Bengkulu and Cilandak, South Jakarta - Yuniarti, Yuniarti; Destariyani, Elvi; Puspita, Erlin; Nurhayati, Nurhayati (EMBRIO: Jurnal Kebidanan, 2025)
ANC results are usually recorded in the MCH book, but pregnant women often forget to bring the book, the applications are really needed to make it easier. The aim of this research is to analyze the effectiveness of implementing My ADA on ANC visit behavior among pregnant women in the cities of Bengkulu and Cilandak, South Jakarta. This research uses a quasi-experimental design. The research will be carried out at PMB Bengkulu City and Cilandak, South Jakarta, a sample of 106. Purposive sampling technique. There was an increase in the average knowledge about ANC in the MY ADA application group and the KIA book group. Which means there is a difference in the average knowledge score between the My ADA application group and the MCH book group (p=0,00), so it can be concluded that the My ADA Application group is more effective in increasing pregnant women's knowledge about ANC.